Matrix metalloproteinase 9 level changes in gingival crevicular fluid samples of teeth with acute and chronic apical periodontitis - Nozhan Azimi; Mohammad Mahdi Khanmohammadi; Sarvin Mesbahian; Mozhgan Khatibzadeh; Mehdi Vatanpour; Amirabbas Moshari (Wolters Kluwer Medknow Publications, 2024)
Background: This study investigates the influence of dental pulp and periapical status on inflammatory mediators, particularly matrix metalloproteinases (MMPs), which contribute to tissue destruction around the teeth and the development of periodontitis. This study aimed to compare MMP-9 levels in the gingival crevicular fluid (GCF) between the cases of acute apical periodontitis, chronic apical periodontitis, and healthy controls before and after root canal treatment (RCT). Materials and Methods: This prospective, cohort study involved 19 samples each of acute and chronic periodontitis cases, both before and after RCT, along with 18 samples from healthy control teeth. The samples were collected from the GCF using paper cones. After 2 weeks of RCT, the process was repeated. MMP-9 levels were measured using the enzyme-linked immunosorbent assay technique. Statistical analysis was performed using the paired t-test and analysis of variance test and the significance level was set at < 0.05. Results: Before treatment, there was no significant difference in MMP-9 levels between the healthy (0.476 μg/μL) and acute (0.48 μg/μL) groups; however, significant differences were observed between the healthy and chronic (0.534 μg/μL) groups. In addition, MMP-9 levels differed significantly between the acute and chronic groups before treatment. Post-treatment, the healthy group showed no notable difference compared to either patient group. However, a significant difference was observed between the acute (0.445 μg/μL) and chronic (0.491 μg/μL) groups after treatment. Conclusion: Our findings suggest that MMP-9 levels in GCF increase during periapical inflammation and decrease after endodontic treatment. MMP-9 may serve as a potential diagnostic biomarker for pulp and periapical inflammation, enhancing our understanding of these clinical conditions and informing future therapeutic strategies.